Absorption spectra of dark interstellar clouds − a long term project for the Terskol Observatory - Krelowski, J.; Musaev, F.A.; Galazutdinov, G.A. (Кинематика и физика небесных тел, 2005)
We present the long-term project on investigation of the absorption spectral features originating in interstellar HI clouds. This project is being realized at the Terskol Observatory. The most important results and the world-largest database of spectra of interstellar clouds are described. The authors are very grateful to the Terskol Observatory staff members for the support during the observations. They also acknowledge the financial support from the NATO collaborative linkage grant PST.CLG.980313. G. A. G. and F. A. M. are grateful to the Russian Foundation for Basic Research (under the grant No. 02–02–17423) and the Federal program “Astronomy” for financial support. G. G. is grateful to the Korean MOST (Ministry of Science and Technology) (grant M1–022–00–0005) and KOSFT for providing an opportunity to work at KAO in the framework of the Brain Pool program.